Defensin from the ornate sheep tick Dermacentor marginatus and its effect on Lyme borreliosis spirochetes - Chrudimská, Tereza; Čeřovský, Václav; Slaninová, Jiřina; Rego, Ryan O M; Grubhoffer, Libor (Developmental and comparative immunology, 2014)
Expression of the previously reported defensin of the tick Dermacentor marginatus (defDM) was analysed in different organs by RT-PCR. mRNA of the defDM gene was detected in the hemolymph, midgut and salivary glands. Moreover defDM was isolated from the tick hemolymph using RP-HPLC and its sequence was determined by mass spectrometry and Edman degradation. Synthetic peptide was used for determining biological activities. The results showed an anti-Gram-positive bacterial role for the defensin. As D. marginatus ticks appear not to be vectors of the Lyme disease agent of the complex Borrelia burgdorferi sensu lato, we tested the influence of defDM on Borrelia afzelii. There is a very clear borrelicidal activity of the defensin, which is concentration dependent and suggests a possible role in the clearing of Borrelia ingested by D. marginatus ticks.
Keywords: Microbial Sensitivity Tests; proteiny členovců; defensiny; Borrelia burgdorferi Group; antifungální látky; Female; mikrobiální testy citlivosti; Defensin; antibakteriální látky; zvířata; Arthropod Proteins; Antimicrobial activity; Tick; ženské pohlaví; Anti-Bacterial Agents; Borrelia burgdorferi komplex; Dermacentor marginatus; Antifungal Agents; antivirové látky; Antiviral Agents; Defensins; Animals; Dermacentor; Borrelia afzelii; Peptide synthesis